Young adults' expressions of contemporary filial piety: development of a young adult filial piety scale - Tay, Celine Shi Qing (Nanyang Technological University, 2023)
Rooted in Confucianism, filial piety (xiao) imparts familial values and guides children how they should treat their parents. Preferential treatment for close kins, reciprocity for favours in close relationships, absolute reverence for the elders and patriarchal familial structures were key characteristics of traditional filial piety. Due to societal changes resulting from industrialization and modernization, shifts in priorities have eroded some practices of filial piety that were bound by the family system. Now, contemporary filial piety is viewed as an unconditional expression of support between parents and children. Prior to becoming regular caregivers for parents, young adults learn to achieve filial maturity and may elicit unique and age-relevant filial behaviours in early adulthood. Although there are existing scales measuring filial piety attitudes and behaviours, there have been no attempts to construct one that can measure concrete current filial behaviours, which would be the aim of the present research. Exploratory factor analysis yielded a 3-factor structure – Affectionate Regard, Respect and Compliance and Dutiful Deference. Overall, the scale displays good psychometric properties and show some utility in predicting outcomes such as psychosocial adjustment and financial support intentions. The young adult filial piety scale has implications on cultivating a better understanding of dynamics in parent-young adult relationships that contribute towards positive familial bonds and psychological outcomes of both parties. Researchers and policymakers can also use the scale to inform social policies. Given its current limitations, future refinements of the scale are warranted.